Observance of the Legal Choice for the Settlement of Indonesia's Past Gross Violations of Human Rights - Subawa, I Made; Hermanto, Bagus; Mas Ratu, Ida Ayu; Mariko Hattori (Yuridika, 2024)
Global developments attempt to rectify serious human rights breaches within the context of legal regulations, as well as to build human rights systems and institutions on a national and global scale. However, in Indonesia, the paradigm shift from authoritarianism to democracy leads human rights as one of most important issues faced by the Indonesia government. In the last two decades, the red record in resolving major human rights abuses has not been attained, necessitating a study to evaluate effective legal choices in settlement of the past human rights violations settlement. This paper employed a statutory method, legal concepts, legal cases, and citations. The comparison validates the direction of this paper's research on the dynamics of national legal concerns in the policy of resolving gross human rights abuses and the selection of law that may be employed in effectively resolving major human rights violations in favor of transitional justice. The obtained results and findings show that problems have emerged in policy orientation at the macro, mezzo, and micro policy strata, as well as the need for future direction in the substance of legislation and the enforcement system, both through judicial and extrajudicial channels, against serious human rights violations.